Comprehensive Course on Clinical Study Data Management for Medical Informatics Students - Ignatenko, Yevgeniia; Ortmann, Natalia; Lutz, Sebastian; Kramer, Frank (Applied Clinical Informatics, 2025)
Background Effective data management is critical in medical informatics research, ensuring the success and integrity of clinical studies. However, students often lack comprehensive training in this area, highlighting the need for tailored educational programs.Objectives This study aims to introduce a proposed course focused on data management for medical informatics students. The objectives include providing students with a robust understanding of data management principles, particularly emphasizing technical measures within clinical studies regarding data quality, interoperability, and extract, transform, and load pipelines.Methods The course design involves a multidimensional approach, covering various aspects of research data management. It comprises each step involved in setting up a clinical trial, based on a real study adapted for educational purposes and presented in a longitudinal stepwise design. An anonymous survey was conducted among the students to evaluate and further develop the course content.Results Initial feedback from students participating in the pilot course has been positive, with 62.5% of responses evaluating this course as “very good.” Students reported an improved understanding of data management principles and expressed appreciation for the practical exercises. Topics include theoretical concepts, practical applications, and hands-on exercises. Lectures, exercises, and interactive sessions are utilized to engage students and enhance learning outcomes. The course structure facilitated active participation and knowledge retention among students.Conclusion The proposed course bridges a gap in the education of medical informatics students between theory and practice, equipping them with technical skills, medical knowledge, and data analytics. The course aims to prepare future professionals to address the complex data challenges inherent in clinical studies, improving clinical research processes for higher-quality evidence. The positive feedback from students underscores the effectiveness, successful implementation of the course, and relevance of such a course in shaping the next generation of medical informatics professionals.
Keywords: education; research data management; fast healthcare interoperability resources; clinical data management; clinical research informatics